Persepsi Masyarakat Pesisir Kota Bandar Lampung Terhadap Hutan Mangrove - Chantika Osfindra Permata; Dian Iswandaru; Rudi Hilmanto; Indra Gumay Febryano (Universitas Bangka Belitung, 2021)
The community perception in urban coastal areas towards the mangrove ecosystem is an important factor in planning its sustainability strategy. This study aims to explain people's perceptions of mangrove forests in Kota Karang district, City of Bandar Lampung. Data collection was carried out by interview using questionnaires and observations. The collected data were analyze using the Likert scale, then it was described quantitatively. The results showed that 50% of people's perceptions of mangroves was medium (neutral) category. This condition occurred because people tend to hesitate in determining their responds towards mangrove forests. The factors that influence community perceptions were lack of knowledge of mangrove, educational levels, awareness and time availability of the community, and also the lack of information about mangrove forests due to the inadequate role of the government in providing the education (counseling) of mangrove. The government is expected to provide education and make policies to increase public awareness towards the importance of preserving mangrove forests.